Assessment of Regeneration Potential in the Clonal Macrophyte Miscanthus sacchariflorus (Poaceae) after Burial Disturbance Based on Bud Bank Size and Sprouting Capacity - Chen, Xinsheng; Cao, Chenshu; Deng, Zhengmiao; Xie, Yonghong; Li, Feng; Hou, Zhiyong; Li, Xu (PLOS ONE, 2015)
The demography of the bud bank and its sprouting capacity are important for understanding the population dynamics of clonal plants and their potential responses to disturbances. To this end, we investigated the size and composition of the bud bank of Miscanthus sacchariflorus (Maxim.) Hack. immediately after flooding (November), in winter (January), in spring (March), and before flooding (May) in the wetlands of Dongting Lake. We then examined the sprouting capacity of axillary buds after sediment burial at 0, 5, 10, 15, and 20 cm. Total bud density of M. sacchariflorus ranged from 2524 buds m-2 in November to 4293 buds m-2 in March. Rhizome segments with inactive axillary buds, which represented the majority of the bud population (88.7% in November, 93.3% in May), did not sprout during the 140 days of the experiment (n = 250). The sprouting ratio was the highest for active axillary buds buried at 0 cm (64%) and decreased when buried at 10–20 cm (34%–40%). Due to the large number of active axillary buds in the bud bank (211–277 buds m-2 from November to the following March), M. sacchariflorus could completely replace its aboveground shoot population, except in May (142 buds m-2). Increasing burial depth delayed bud emergence and reduced the growth period of shoots; however, burial depth did not affect the resulting plant height and only reduced the accumulated biomass at 20 cm. Therefore, the belowground bud bank and its strong sprouting capacity are important factors in the maintenance of local populations and colonization of new habitats for M. sacchariflorus after burial disturbances. The present methodology, which combined measurements of bud bank demography and sprouting capacity, may reflect the regeneration potential of clonal plants after burial disturbances.